Numerical simulation of thermal pollution zones' formations in the water environment from the activities of the power plant. Issue 1 (1st January 2019) - Issakhov, Alibek; Zhandaulet, Yeldos
ABSTRACT: In this paper, obtained numerical results of the thermal pollution from the operation of a power plant are presented when using the Irtysh River as a natural water cooling system. A two-dimensional formulation by using the "shallow water" approximation is often used as a numerical solution of such problems. For two-dimensional numerical modeling, it is possible to determine the floating flow together with its characteristics of mixing heated water discharge from lateral projections to transverse flow. Furthermore, data from the experiment and numerical values of other authors were used in order to check the conformity of the computational results. The obtained numerical values gave good agreement comparing with data from the experiment, specially the jets trajectory, the recirculation zones size and the dimensionless excess temperature distribution. The obtained data as a result of numerical simulation can be used to study problems associated with the mixing of heated water discharged from the lateral direction into the transverse flow. Also these studies were conducted to study thermal contamination under different scenarios, the impact of heated water discharge from a power plant in the Irtysh River, and the areas of thermal pollution for different velocity scenarios were determined.